Preliminary phase in the process of social innovation with agricultural and milk producers of Viracachá - Boyacá - Yineth Ochoa Rodríguez (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This project addresses the development of the preliminary stage in a process of social innovation was to build a socio-cultural and economic profile of the community involved with agricultural production and milk in the town of Viracachá, and accordingly is developing a process support, assistance and advice to those producers to build social capital that has allowed them to make an organizational strategy and a business model that articulates this local productive activity with national value chains.